Design and hybrid impedance control of a new compliant wrist rehabilitation device. (June 2023) - Yellewa, Mwayi E; Mohammed, Abdelfatah; Ishii, Hiroyuki; Assal, Samy FM
Over a decade, wrist rehabilitation robots have been proved to be efficient in the rehabilitation of patients with stroke or wrist injuries. Wrist rehabilitation devices compensate for deficiencies in manual rehabilitation training and reduce the workload of physiotherapists with their repetitive and gradual training necessary to rehabilitate patients with wrist impairments properly. Two design approaches have been reported in literature for wrist rehabilitation robotic devices. In one design approach, the strategy of placing the actuators, either linear or rotary, on the forearm to minimise the weight and inertia has been proposed. This necessitates a use of sophisticated transmission systems. In the other design approach, rotary motors have been proposed to be placed directly on the wrist joints, which results in a high weight and inertia. In this paper, a new 2-DOF compliant wrist rehabilitation device that can achieve the flexion-extension and radial-ulnar rehabilitation movements compliantly is proposed. In the proposed design, two series elastic actuators (SEAs), each consists of a servomotor and a custom-designed series elastic unit, are proposed to be placed directly on the wrist joints. In order to minimise the inertia and the required torques, the device is counterweight balanced by optimising the centre of mass of the device in the SolidWorks model. Based on the device dynamics modelled by ADAMS software, hybrid position and force tracking impedance control with the incorporation of a disturbance observer controller for the rotary SEA is developed for position and force tracking through the different therapeutic exercises. The disturbance observer controller is incorporated for high precision force control and robustness against exogenous disturbances. Simulation results demonstrate high performance of the proposed wrist rehabilitation device in terms of precise position and force trajectories tracking and robustness against exogenous disturbance as well as patient safety during all therapeutic exercises.